My age of anxiety : fear, hope, dread, and the search for peace of mind - Stossel, Scott (Alfred A. Knopf, 2013)
The author recounts his lifelong battle with anxiety, showing the many manifestations of the disorder as well as the countless treatments that have been developed to counteract it, and provides a history of the efforts to understand this common form of mental illness.